A flow-through optical fibre reflectance sensor for the detection of lead ion based on immobilised gallocynine - Yusof, Nor Azah; Ahmad, Musa (Elsevier, 2003)
A flow-through spectrophotometric sensor for the determination of lead at trace level using immobilised gallocynine as the reagent phase is proposed. Gallocynine is physically adsorbed onto XAD-7. This method provided a wide linear range of 1 × 10-1 to 1 × 103 ppm and detection limit of 0.06 ppm. This method also showed a reproducible result with relative standard deviation (R.S.D.) of 1.64% and response time of ∼5 min. The response towards lead was also reversible using acidified KNO3 as the regenerating solution. Interference studies showed that Hg(II) and Ag(I) significantly interfered during the determination.